A revised systematic review and meta‐analysis on the effect of statins on D‐dimer levels. (3rd June 2019) - Schol‐Gelok, Suzanne; Morelli, Francesca; Arends, Lidia R.; Boersma, Eric; Kruip, Marieke J. H. A.; Versmissen, Jorie; van Gelder, Teun
Abstract: Background: D‐dimers are generated during endogenous fibrinolysis of a blood clot and have a central role in diagnostic algorithms to rule out venous thromboembolism. HMG‐CoA reductase inhibitors, more commonly called statins, are known to have effects independent of LDL‐cholesterol lowering, including antithrombotic properties. An effect of statins on D‐dimer levels has been reported in a prior systematic review and meta‐analysis, but methodological shortcomings might have led to an overestimated effect. To re‐evaluate the association between statins and D‐dimer levels, we systematically reviewed all published articles on the influence of statins on D‐dimer levels and conducted a novel meta‐analysis (PROSPERO registration number CRD42017058932). Materials and methods: We electronically searched EMBASE, Medline Epub, Cochrane, Web of Science and Google Scholar (100 top relevance) (date of last search: 5 October 2017). We included randomized controlled trials, cohort studies and cross‐sectional studies. Two reviewers independently screened all articles retrieved and extracted data on study and patient characteristics, study quality and D‐dimer levels. Results: Study‐level meta‐analysis involving 18, 052 study participants showed lower D‐dimer levels in those receiving statin treatment than controls (SMD: −0.165, 95% CI −0.234; −0.096, P = <0.001). Sensitivity analyses and additional analyses on treatment duration (<12 weeks vs ≥12 weeks) and type of statin (lipophilic or hydrophilic) did not modify this overall result. Conclusion: This meta‐analysis suggests an association between use of statins and reduction of D‐dimer levels, independent of treatment duration and type of statin used. This effect is small but robust, and should be interpreted with caution.